2019
DOI: 10.1038/s41467-019-12896-x
|View full text |Cite
|
Sign up to set email alerts
|

Theabrownin from Pu-erh tea attenuates hypercholesterolemia via modulation of gut microbiota and bile acid metabolism

Abstract: Pu-erh tea displays cholesterol-lowering properties, but the underlying mechanism has not been elucidated. Theabrownin is one of the most active and abundant pigments in Pu-erh tea. Here, we show that theabrownin alters the gut microbiota in mice and humans, predominantly suppressing microbes associated with bile-salt hydrolase (BSH) activity. Theabrownin increases the levels of ileal conjugated bile acids (BAs) which, in turn, inhibit the intestinal FXR-FGF15 signaling pathway, resulting in increased hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
393
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 563 publications
(464 citation statements)
references
References 45 publications
22
393
4
1
Order By: Relevance
“…These results prompt us to anticipate that IBS is a disease with moderate alterations in fecal microbiota and metabolites. Moreover, tea drinking was observed to be associated with fecal microbiota and metabolites in IBS, which is consistent to previous study that tea could have effect on gut microbiota [32]. However, more detail relationship between tea and IBS are needed in further research.…”
Section: Discussionsupporting
confidence: 88%
“…These results prompt us to anticipate that IBS is a disease with moderate alterations in fecal microbiota and metabolites. Moreover, tea drinking was observed to be associated with fecal microbiota and metabolites in IBS, which is consistent to previous study that tea could have effect on gut microbiota [32]. However, more detail relationship between tea and IBS are needed in further research.…”
Section: Discussionsupporting
confidence: 88%
“…59 Polyphenols extracted from puerarin (Pueraria lobata), resveratrol, and quercetin can mediate cholesterol efflux and intestinal microbial changes, thereby regulating bile acid excretion and reducing fat production. 60,61 Scutellaria baicalensis can increase the expression of the rate-limiting enzyme cytochrome P450 family 7 subfamily A member 1 (CYP7A1) in the bile acid biosynthesis pathway, and CYP7A1 can prevent the obesity induced by a high-fat diet (the exact mechanism is not clear). 62 Clove, allspice, and aromatic ginger extracts can induce TGR5-mediated BAS weight loss effects.…”
Section: Regulate the Levels Of Bile Acids And Other Metabolitesmentioning
confidence: 99%
“…Gut bacteria play a profound role in BAs metabolism and are responsible for the modification of BAs via promoting deconjugation, dehydrogenation, and dehydroxylation of primary BAs 9 . Numerous studies have shown that gut microbiota can regulate host physiology by altering BAs metabolism 10‐12 . In addition, the altered BAs metabolism profiles have been considered as a marker of many diseases, such as IBD, Crohn's disease, and Alzheimer's disease 13‐15 …”
Section: Introductionmentioning
confidence: 99%